Person to person customer service [videorecording] - Video Education Australasia (New York, N.Y. Films Media Group, 2012)
This video shows employees how to achieve that goal, using lively animation, no-nonsense explanations, and clear, entertaining dramatizations. Topics include creating a good first impression, developing a professional and outgoing attitude, following customer service procedures in a logical manner, and handling conflict calmly, confidentially, and respectfully.
DVD
Keywords: Customer services; Business communication; Business etiquette; Business logistics; ommunication; Interpersonal communication; Office practice